Effectiveness of Haemophilus influenzae type b Conjugate vaccine introduction into routine childhood immunization in Kenya. - Cowgill, K; Ndiritu, M; Nyiro, J; Slack, M; Chiphatsi, S; Ismail, A; Kamau, T; Mwangi, I; English, M; Newton, C; Feikin, DR; Scott, J (2006)
CONTEXT: Haemophilus influenzae type b (Hib) conjugate vaccine is not perceived as a public health priority in Africa because data on Hib disease burden and vaccine effectiveness are scarce. Hib immunization was introduced in Kenyan infants in 2001. OBJECTIVE: To define invasive Hib disease incidence and Hib vaccine program effectiveness in Kenya. DESIGN, SETTING, AND PATIENTS: Culture-based surveillance for invasive Hib disease at Kilifi District Hospital from 2000 through 2005 was linked to demographic surveillance of 38,000 children younger than 5 years in Kilifi District, Kenya. Human immunodeficiency virus (HIV) infection and Hib vaccination status were determined for children with Hib disease admitted 2002-2005. INTERVENTIONS: Introduction of conjugate Hib vaccine within the routine childhood immunization program at ages 6, 10, and 14 weeks beginning November 2001. MAIN OUTCOME MEASURES: Incidence of culture-proven Hib invasive disease before and after vaccine introduction and vaccine program effectiveness. RESULTS: Prior to vaccine introduction, the median age of children with Hib was 8 months; case fatality was 23%. Among children younger than 5 years, the annual incidence of invasive Hib disease 1 year before and 1 and 3 years after vaccine introduction was 66, 47, and 7.6 per 100,000, respectively. For children younger than 2 years, incidence was 119, 82, and 16 per 100,000, respectively. In 2004-2005, vaccine effectiveness was 88% (95% confidence interval, 73%-96%) among children younger than 5 years and 87% (95% confidence interval, 66%-96%) among children younger than 2 years. Of 53 children with Hib admitted during 2002-2005, 29 (55%) were age-ineligible to have received vaccine, 12 (23%) had not been vaccinated despite being eligible, and 12 (23%) had received 2 or more doses of vaccine (2 were HIV positive). CONCLUSIONS: In Kenya, introduction of Hib vaccine into the routine childhood immunization program reduced Hib disease incidence among children younger than 5 years to 12% of its baseline level. This impact was not observed until the third year after vaccine introduction.